Spinal involvement in gout simulating spondyloarthritis (clinical case) - Y. I. Kuzmina; M. S. Eliseev (Современная ревматология)
The article presents a case of the lumbar spine involvement in a 37-year-old patient with gout who was observed for several years with a diagnosis of spondyloarthritis. Spinal involvement in the context of gout was confirmed by dual-energy computed tomography. This is a relatively new method for the diagnosis of microcrystalline arthritis, which makes it possible to detect urate deposits in the atypical course of the disease, especially when the axial skeleton is affected. We demonstrate the advantages of the modern gout treatment strategy of achieving and maintaining target uric acid levels by prescribing appropriate doses of xanthine oxidase inhibitors (febuxostat at a dose of 120 mg/day) while preventing arthritis flares (low-dose colchicine).